Arduino Uno Microcontroller Programming as a Timer for Hotplate Magnetic Stirrers - irwan Nova; Ana Uzla BatuBara; Mandapot Tua Naibaho (International Journal of Health Engineering and Technology, 2026)
Based on the title above, this scientific paper aims to analyze the Arduino Uno programming on the Magnetic Stirrer Hotplate tool with the addition of a timer. The Magnetic Stirrer Hotplate functions to homogenize the solution at a certain temperature, rpm and time. If the set timer has been reached, the buzzer will turn on, which aims to let the operator or user know that the tool has finished mixing the chemicals. The results of the microcontroller programming test on the timer control circuit using the C++ language were successfully carried out and the circuit functioned according to the programming instructions..